2014
DOI: 10.2106/jbjs.m.01218
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary and Radiographic Outcomes of VEPTR (Vertical Expandable Prosthetic Titanium Rib) Treatment in Early-Onset Scoliosis

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 29 publications
3
13
0
1
Order By: Relevance
“…Dede et al reported that the use of VEPTR in children with early-onset scoliosis due to a variety of conditions led to large improvements in FVC (a 45% improvement (0.31 L) at 72 months). [19] However, similar to our results, these children had reduced percent predicted FVC (77% to 58%). [19] Other work however, has shown increases in percent predicted FVC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Dede et al reported that the use of VEPTR in children with early-onset scoliosis due to a variety of conditions led to large improvements in FVC (a 45% improvement (0.31 L) at 72 months). [19] However, similar to our results, these children had reduced percent predicted FVC (77% to 58%). [19] Other work however, has shown increases in percent predicted FVC.…”
Section: Discussionsupporting
confidence: 88%
“…[19] However, similar to our results, these children had reduced percent predicted FVC (77% to 58%). [19] Other work however, has shown increases in percent predicted FVC. A study of six children with neuromuscular disease with magnetic growing rods showed an improvement of 14% percent predicted FVC at an average of 30 months of follow-up.…”
Section: Discussionsupporting
confidence: 88%
“…55 With longer periods of follow-up (mean 6 years) during and at the completion of growing construct surgery, FVC as a percentage of normal declined by an average of 28%. 56,57 There are no untreated control groups to assess what loss of lung function might have occurred in the natural progression of the spine deformities. The implication of these studies is that lung function is not normalized or predictably improved after treatments for EOS but that progressive loss of lung function may be reduced with treatment.…”
Section: Pulmonary Outcomes Of Recent Eos Treatmentmentioning
confidence: 99%
“…15,20,23 Studies on spine distraction showed increased spine kyphosis following repeated lengthening. 15,20,23 Studies on spine distraction showed increased spine kyphosis following repeated lengthening.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] Despite these benefits, a concern has been raised that serial posterior distraction surgeries may progressively lead to less spine growth. 14,16,23 Subsequently, VEPTR has been applied to other spine conditions including EOS without ribs anomalies. The authors demonstrated that most scoliosis correction and length gain was achieved at the time of initial implantation followed by lower gain with the subsequent lengthening surgeries.…”
mentioning
confidence: 99%